Triterpenic saponins from Medicago marina L. (June 2020) - Tava, Aldo; Biazzi, Elisa; Ronga, Domenico; Mella, Mariella; Doria, Filippo; Accogli, Rita; Argentieri, Maria Pia; Avato, Pinarosa
Abstract: The saponin composition of leaves and roots from Medicago marina L., sea medic, was investigated by a combination of chromatographic, spectroscopic and spectrometric (GC, LC, ESI-MS/MS, NMR) methods. Several compounds were detected and quantified by HPLC using the external standard method. Saponins from this plant species consist of a mixture of high molecular weight bidesmosidic derivatives of medicagenic and zanhic acid, containing up to six sugars in the molecules. Six of the detected saponins were previously isolated and reported as constituents of other Medicago spp.; one saponin was previously described in other plant species; four saponins are undescribed compounds in Medicago and never reported before in other plant species. These are: 3- O - β -D-glucopyranosyl-(1 → 2)- β -D-glucopyranosylzanhic acid 28- O - β -D-xylopyranosyl-(1 → 4)-[ β -D-apiofuranosyl-(1 → 3)]- α -L-rhamnopyranosyl-(1 → 2)- α -L-arabinopyranosyl ester; 3- O - β -D-glucopyranosyl-(1 → 2)- β -D-glucopyranosylzanhic acid 28- O - β -D-xylopyranosyl-(1 → 4)- α -L-rhamnopyranosyl-(1 → 2)- α -L-arabinopyranosyl ester; 3- O - β -D-glucopyranosyl-(1 → 2)- β -D-glucopyranosylmedicagenic acid 28- O - β -D-xylopyranosyl-(1 → 4)-[ α -L-arabinopyranosyl-(1 → 3)]- α -L-rhamnopyranosyl-(1 → 2)- α -L-arabinopyranosyl ester and 3- O - β -D-glucopyranosylmedicagenic acid 28- O - β -D-xylopyranosyl-(1 → 4)-[ α -L-arabinopyranosyl-(1 → 3)]- α -L-rhamnopyranosyl-(1 → 2)- α -L-arabinopyranosyl ester. The specific saponins synthesized by M. marina may have a role in its tolerance to environment, representing a reservoir of osmolytic sugars. Graphical abstract: Image 1 Highlights: Saponins from leaves and roots of M. marina L. have been investigated. The specific saponins sythesized by this plant may have a role in its tolerance to environment. These compounds may represent a reservoir of osmolytic sugars.